Burnout and Dropout Analysis Of Badminton Adolescence Athletes: Reviewed in Psychological Aspect (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The goals of the research are: 1) to find out why adolescent badminton atheletes burnout and dropout; 2) to analyzing the psychological characteristics of adolescent athletes who burnout and dropout; and 3) to analyzing solutions and strategies for burnout and dropout athletes. With a convergent or concurrent approach, the research design is a mix of different methods. Data collection techniques using questionnaires, interviews, documentation, and observation. The SPSS statistical application for Windows version 23.0 and the NVivo 10 software were used to analyze the data. The results of the study showed that burnout in athletes was caused by lack of training variety, too fast specialization, intense training, a lot of pressure, and psychological instability. Meanwhile, dropouts are caused by the focus on education, difficulty in dividing time, switching sports, burnout, early specialization, feel too much pressure, have a negative impression, and environmental influence. Psychological characteristics of burnout athletes are categorized as very high motivation, self-confidence and mental preparation are categorized as high, while anxiety control, concentration, and the importance of the team is categorized as moderate. Dropout athletes are categorized as very low motivation and concentration, very low concentration category, self-confidence and team importance are categorized as moderate, anxiety control and mental preparation are categorized as low. Solutions and strategies for adolescent athletes are support and mentoring of parents and coaches, improving coaches' psychological skills, a comfortable environment for athletes, and support from the government and parent organizations.